A randomized controlled trial of an internet-delivered treatment: Its potential as a low-intensity community intervention for adults with symptoms of depression. (December 2015) - Richards, D.; Timulak, L.; O'Brien, E.; Hayes, C.; Vigano, N.; Sharry, J.; Doherty, G.
Abstract: Background: Internet-delivered treatments for depression have proved successful, with supported programs offering the potential for improved adherence and outcomes. Internet interventions are particularly interesting in the context of increasing access to interventions, and delivering interventions population-wide. Methods: The study was a randomized controlled trial of an 7-module internet-delivered cognitive behavioral therapy (iCBT) program for adults with depressive symptoms ( n  = 96) compared to a waiting-list control group ( n  = 92). Participants received weekly support from a trained supporter. The primary outcome was depressive symptoms as measured by the Beck Depression Inventory (BDI-II). The program was made available nationwide from an established and recognized charity for depression. Results: For the treatment group, post-treatment effect sizes reported were large for the primary outcome measure ( d  = 0.91). The between-group effects were moderate to large and statistically significant for the primary outcomes ( d  = 0.50) favoring the treatment group. Gains were maintained at 6-month follow-up. Conclusion: The study has demonstrated the efficacy of the internet-delivered Space from Depression treatment. Participants demonstrated reliable and statistically significant changes in symptoms from pre-to post-intervention. The study supports a model for delivering online depression interventions population-wide using trained supporters. Trial registration number : Current Controlled Trials ISRCTN03704676. http://dx.doi.org/10.1186/ISRCTN03704676. Highlights: The study demonstrated the potential of an internet-delivered treatment with support in a community sample. It gives support to a model for delivering population-wide internet-interventions for depression using trained supporters. The volunteers' community of practice may be significant for the success of internet-interventions in the community. Dose and response in internet-delivered interventions is an area that requires further research.